PRELIMINARY SCREENING OF PHYTOCHEMICAL CONSTITUENTS, ANTIOXIDANT, AND ANTI-BACTERIAL ACTIVITIES IN THE METHANOLIC LEAF EXTRACT OF MELIOSMA SIMPLICIFOLIA (L.) - S, PAVITHRA; T, SEKAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: In the present study is investigated of phytochemicals and antioxidant activities of the leaf extracts from Meliosma simplicifolia (L.). Methods: The seaweed sample was subjected to extraction with solvents of different polarities (hot water, methanol, acetone, chloroform, and petroleum ether) and screened for phytochemicals according to standard methods. The ability of the plant extract to act as hydrogen/electrons donor or scavenger of radicals was determined by in vitro antioxidant assays using 2,2-diphenyl-2-picryl-hydrazyl free radical (DPPH) scavenging, reducing power assay, and superoxide radical (O2•) scavenging activity. The ICPMS and GC-MS analysis of the methanol leaf extract of M. simplicifolia was revealed the presence of antibacterial. Results: Phytochemical analysis revealed the presence of Preliminary metabolites Quantitative studies of estimated phenol, flavonoid and tannin, as for the methanol extract of stem showed the highest content of phenolic compounds (40.71±0.94 GAE mg/100). Antioxidant activities were concluded the estimation M. simplicifolia leaf for as followed the studies. In leaf the highest DPPH scavenging activity (132.3 μg/ml), ICP-MS analysis of the leaf extract showed the presence minerals such as Mg, Fe, Cu, Na, and Zn in excess. The leaf extract of the plant was also tested for its antibacterial activity and results confirmed that it has potential activity. Conclusion: The preliminary studies in the methanol extract of the leaf of M. simplicifolia are suggestive of the antibacterial potentials of the methanol extract of leaves of M. simplicifolia.